2002
DOI: 10.1074/jbc.m204393200
|View full text |Cite
|
Sign up to set email alerts
|

Tat HIV-1 Primary and Tertiary Structures Critical to Immune Response Against Non-homologous Variants

Abstract: Clinical studies show that in the absence of anti-retroviral therapy an immune response against the human immunodeficiency virus type 1 (HIV-1), transacting transcriptional activator (Tat) protein correlates with long term non-progression. The purpose of this study is to try to understand what can trigger an effective immune response against Tat. We used five Tat variants from HIV strains identified in different parts of the world and showed that mutations of as much as 38% exist without any change in activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
50
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 37 publications
(41 reference statements)
7
50
0
Order By: Relevance
“…We also observed that at all concentrations tested, there was no significant difference between the three variants except at 400 nM, the highest concentration tested where both subtype C Tat proteins had a higher activity (data not shown). This difference agrees with previously published data using different cell lines (28,44,57,66 (Fig. 1B) and Tat 96Bw (data not shown) elicited a transient increase in [Ca 2ϩ ] i in monocytes that returned to baseline 1 minute after the initial flux.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…We also observed that at all concentrations tested, there was no significant difference between the three variants except at 400 nM, the highest concentration tested where both subtype C Tat proteins had a higher activity (data not shown). This difference agrees with previously published data using different cell lines (28,44,57,66 (Fig. 1B) and Tat 96Bw (data not shown) elicited a transient increase in [Ca 2ϩ ] i in monocytes that returned to baseline 1 minute after the initial flux.…”
Section: Resultssupporting
confidence: 82%
“…However, recent research has shown that the different genetic subtypes and recombinant forms of HIV-1 have biological differences with respect to transmission, replication, and disease progression (14,47,74,85). Moreover, different subtypes of Tat have different in vitro effects (17,18,27,28,57,62,66,67,76).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous data showed that native Tat enters MDDC, induces their maturation, and promotes their capacity of presenting Ag through the preferential development of a Th1-type immune response (15). This body of evidence prompted us to further investigate the apparent intrinsic adjuvanticity of Tat by exploring the effects of the native, wt Tat protein compared with those of cys22 Tat, a naturally occurring Tat mutant originated from a long-term non-progressor individual (31), which induced high titers of antiTat Ab (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Another important feature of Tat rendering it a relevant vaccine antigen is the conservation of its immunogenic regions among the HIV-1 M group at the sequence, functional, and conformational level [120,142,151,152,154,163]. Indeed, the Tat protein of 86 aa from a clade B lab-adapted HIV-1 virus (HTLV-IIIB strain, clone BH-10) isolated more than 20 years ago [164] is very well recognized by sera from African individuals infected with different virus clades, including clade C, which is responsible for more than half of new HIV-1 infections worldwide [165], with similar prevalence and epitope mapping titers of anti-Tat antibodies [120].…”
Section: The Choice Of Tat As Vaccine Relevant Antigenmentioning
confidence: 99%